Preparation method and application of sodium ion battery hard carbon negative electrode material
Patent Information
- Application Number
- CN202410486655.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-23
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-04-23
AI Technical Summary
[0004]为解决目前钠离子电池负极材料原料成本高、工艺复杂、生产能耗高及兰炭的增值利用等问题,本发明提供了一种以兰炭为原料制备钠离子电池负极材料的方法和应用
[0027]1.本发明以廉价易得的兰炭粉末作为碳源生产钠离子电池负极材料,实现了兰炭小料的高附加值利用。
Smart Images

Figure CN118419897B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sodium-ion battery electrode material technology, and particularly relates to a method for preparing and applying a sodium-ion battery negative electrode material. Background Technology
[0002] Sodium-ion batteries, as a key energy storage system, have become a research hotspot due to their advantages such as high energy density, good cycle stability, and low cost. Hard carbon, as one of the anode materials for sodium-ion batteries, has attracted much attention due to its abundant resources, low cost, and good electrochemical performance. Pyrolytic hard carbon materials based on polymers such as phenolic resins can achieve capacities up to 330 mAh·g. -1 The above. However, the complex synthesis processes and low yields of these materials result in high production costs, posing a challenge to large-scale industrialization. Although biomass materials possess abundant precursor resources and good electrochemical performance, their yields are low and the stability of raw material sources is problematic due to significant regional and seasonal influences. Semi-coke, also known as semi-coke, is a product obtained by pyrolyzing coal at 600-700℃. It has a high fixed carbon content and low volatile matter, but the large amount of fine particulate matter generated during its production and transportation causes resource waste and environmental pollution. If semi-coke can be converted into hard carbon materials for sodium-ion batteries, it would not only provide a high-value-added utilization path for semi-coke but also offer a new raw material option for sodium-ion battery anode materials.
[0003] CN116239099A describes pre-carbonization and high-temperature sintering of semi-coke powder. This patent requires a significant amount of time for repeated heating and cooling in a high-temperature furnace and consumes a large amount of electricity. Then, acid washing and deashing are performed. The acid washing and deashing process involves sequentially using hydrochloric acid and hydrofluoric acid to wash and deash the semi-coke particles. The highly toxic hydrofluoric acid washing poses a safety hazard. Summary of the Invention
[0004] To address the current challenges of high raw material costs, complex processes, high energy consumption, and value-added utilization of semi-coke in sodium-ion battery anode materials, this invention provides a method and application for preparing sodium-ion battery anode materials using semi-coke as a raw material. This method utilizes inexpensive and readily available raw materials, employs a simple process, eliminates the need for artificial control of the oxidation atmosphere, and is suitable for large-scale production. Furthermore, the prepared sodium-ion battery anode material exhibits advantages such as high coulombic efficiency, stable long-cycle performance, and high capacity.
[0005] The technical solution of the present invention:
[0006] A method for preparing a hard carbon anode material for sodium-ion batteries includes the following steps:
[0007] (1) Mechanically crush the semi-coke particles, soak them in concentrated hydrochloric acid solution and stir to acid wash; filter the semi-coke powder treated with hydrochloric acid solution, wash it with water until neutral, and dry it;
[0008] (2) Perform pre-oxidation at a temperature of 250-350℃ for 2-6 hours;
[0009] (3) Under an inert atmosphere, the pre-oxidized semi-coke powder is heated to 800-1000℃ and held for the first stage of carbonization. Then, it is heated to 1200-1600℃ and held for the second stage of carbonization to obtain the hard carbon anode material for sodium-ion batteries.
[0010] A method for preparing a hard carbon anode material for sodium-ion batteries includes the following steps:
[0011] (1) Crush the semi-coke material, soak it in concentrated hydrochloric acid solution and stir to wash it; filter the semi-coke powder treated with hydrochloric acid solution, wash it with water until neutral, and dry it; the crushing method is mechanical crushing, vibrating ball milling or high-energy ball milling.
[0012] (2) Under an inert atmosphere, the acid-washed semi-coke powder is heated to 800-1000℃ and held for the first stage of carbonization, and then heated to 1200-1600℃ and held for the second stage of carbonization.
[0013] (3) Perform post-oxidation treatment at a temperature of 250-350℃ for 2-6 hours to obtain sodium-ion battery hard carbon anode material.
[0014] The present invention provides a method for preparing sodium-ion battery anode materials. It investigates the effect of oxidation sequence on material properties, eliminating the traditional high-temperature furnace pre-oxidation step involving an oxygen-containing atmosphere. Furthermore, it replaces pre-carbonization with a continuous carbonization step, preserving more active sites and saving time and energy costs during cooling and heating processes. This method offers advantages such as simple operation, environmental friendliness, high efficiency, and high yield.
[0015] The semi-coke powder in step (1) is obtained by crushing and sieving blocky semi-coke particles with a particle size ≥100 mesh. The semi-coke particles are semi-coke from Hami region of Xinjiang Uygur Autonomous Region or Shenmu region of Shaanxi Province, preferably from Hami region, with a particle size of 6-13 mm.
[0016] The concentration of the concentrated hydrochloric acid is 4-6 mol / L, the pickling temperature is 25-40℃, and the treatment time is 8-12 h.
[0017] The pre-oxidation heating rate is 1-5℃ / min. -1 The pre-oxidation atmosphere is air.
[0018] The post-oxidation heating rate is 1-5℃ / min. -1 The oxidizing atmosphere is then changed to air.
[0019] The carbonization heating rate is 1-5℃ / min. -1The holding time for both the first and second carbonization stages is 1-3 hours, and the protective atmosphere is argon or nitrogen.
[0020] This also includes maintaining the furnace temperature at 1-5℃ / min after the second carbonization stage is completed. -1 The cooling rate drops to 800-1000℃, and then it cools naturally to room temperature.
[0021] The present invention also provides an electrode material, comprising a conductive agent, a binder, and the above-mentioned sodium-ion battery hard carbon anode material.
[0022] The conductive agent is CNT, Ketjen Black, or SP; the binder is sodium alginate or PVDF.
[0023] The mass ratio of the sodium-ion battery hard carbon anode material, conductive agent, and binder is 70:15:15-90:5:5.
[0024] The present invention also provides a negative electrode sheet for a sodium-ion battery, comprising a current collector and an electrode material coated on the current collector.
[0025] The current collector is a copper foil or an aluminum foil.
[0026] Compared with existing materials or technologies, the present invention has the following advantages:
[0027] 1. This invention uses inexpensive and readily available semi-coke powder as a carbon source to produce sodium-ion battery anode materials, realizing the high added value utilization of semi-coke scrap.
[0028] 2. This invention uses only hydrochloric acid pickling, eliminating the need for the toxic hydrofluoric acid pickling step, which is beneficial for safe production.
[0029] 3. This invention uses a simple air pre-oxidation or post-oxidation method, eliminating the need for additional expensive high-temperature furnace equipment, air intake lines, and manual control of the oxidation atmosphere flow, thus saving economic and time costs.
[0030] 4. The present invention uses a segmented continuous carbonization method to replace the step of pre-carbonization and cooling followed by high-temperature carbonization, which saves a lot of time, reduces energy consumption, and retains more active sites.
[0031] 5. After mechanically pulverizing semi-coke, the pre-oxidation treatment and continuous carbonization process promote the formation of carbon microspheres while preventing their rapid melting at high temperatures. This results in the in-situ growth of uniformly shaped pitch-based carbon microspheres on the surface of the semi-coke-based hard carbon. These microspheres exhibit high bulk density, smooth and uniform surface, small specific surface area, and stable structure, offering advantages such as high coulombic efficiency and stable long-cycle performance. The current density is 0.02Ag. -1 At that time, the sodium storage capacity was 302 mAh g. -1 0.05Ag -1 and 0.5Ag-1 After 500 cycles, the capacity retention rate is greater than 80%.
[0032] 6. Post-oxidation treatment results in abundant oxygen-containing functional groups on the surface of hard carbon materials, providing numerous surface adsorption sites for sodium ions. This leads to an increase in the slope capacity ratio and improves the rate performance of the material under high current (2Ag). -1 The sodium storage capacity at the current density is 50 mAh·g -1 It is suitable for power-type energy storage needs. Attached Figure Description
[0033] Figure 1 This is a scanning electron microscope image of the sodium-ion battery anode material prepared in Example 2;
[0034] Figure 2 The image shows the XRD pattern of the sodium-ion battery anode material prepared in Example 2.
[0035] Figure 3 This is a schematic diagram of the first-cycle charge-discharge curve of the sodium-ion battery anode material prepared in Example 2;
[0036] Figure 4 This is a discharge rate performance diagram of the sodium-ion battery anode material prepared in Example 2;
[0037] Figure 5 This is a graph showing the long-cycle performance of the sodium-ion battery anode material prepared in Example 2;
[0038] Figure 6 This is a discharge rate performance diagram of the sodium-ion battery anode material prepared in Example 5;
[0039] Figure 7 This is a scanning electron microscope image of semi-coke particles;
[0040] Figure 8 This is a graph showing the long-cycle performance of the sodium-ion battery anode material prepared in Comparative Example 3.
[0041] Figure 9 This is a scanning electron microscope image of the sodium-ion battery anode active material prepared in Comparative Example 4;
[0042] Figure 10 This is a scanning electron microscope image of the sodium-ion battery anode active material prepared in Comparative Example 5. Detailed Implementation
[0043] The technical solution of the present invention will be further described below with reference to specific embodiments, but the present invention is not limited to these embodiments.
[0044] The following examples use semi-coke from Hami region of Xinjiang Uygur Autonomous Region.
[0045] Example 1
[0046] According to the preparation method of the sodium-ion battery hard carbon anode material of this embodiment, using semi-coke as raw material, the following steps are included in sequence:
[0047] (1) The semi-coke particles are mechanically crushed and screened through a 100-mesh sieve to obtain semi-coke powder.
[0048] (2) Add 4g of the semi-coke powder obtained in step (1) to 6mol / L concentrated hydrochloric acid and stir magnetically in a water bath at 35℃ for 12h.
[0049] (3) Wash the acid-treated semi-coke powder obtained in step (2) with water until neutral, and dry it to obtain acid-washed semi-coke powder.
[0050] (4) Place the pickled semi-coke powder obtained in step (3) into a muffle furnace and heat it at 3°C for 3 minutes under an air atmosphere. -1 The temperature was increased to 300℃ at a certain rate and held at this temperature for 2 hours, and then allowed to cool naturally to room temperature to obtain pre-oxidized semi-coke powder.
[0051] (5) Place the pre-oxidized semi-coke powder obtained in step (4) into a tubular carbonization furnace, and oxidize it at 3°C for 3 minutes under an argon atmosphere. -1 The temperature was increased to 1000℃ at a heating rate and held at this temperature for 2 hours, then continued at a rate of 3℃ / min. -1 The temperature was increased to 1300℃ at a heating rate and held at this temperature for 2 hours, then increased at a rate of 2℃ / min. -1 The temperature was lowered to 1000℃ at a cooling rate, and then allowed to cool naturally to room temperature to obtain a hard carbon anode material for sodium-ion batteries.
[0052] The hard carbon material obtained in step (5) was mixed with CNTs and sodium alginate binder (3.3% by mass) in a mass ratio of 8:1:1. The mixture was then loaded onto a copper foil current collector, vacuum dried for 12 hours, and cut into 12mm diameter discs for use as the negative electrode of the sodium-ion battery. The average mass loading of the active material was 1.5mg. The battery was then assembled in a glove box using a sodium disc as the counter electrode and glass fiber as the separator to obtain a CR2032 button cell. The assembled CR2032 button cell was left to stand in a constant temperature chamber for at least 12 hours before electrochemical performance testing. In this embodiment, a Land 2001A tester was used for constant current charge-discharge testing, with a metallic sodium disc as both the counter and reference electrode, and a voltage window of 0.01–3.00V. The test results showed that the material exhibited good electrochemical performance at a current density of 0.02A g. -1 At that time, its capacity was 259mAh g. -1 The first lap efficiency was 83.6%.
[0053] Example 2
[0054] According to the preparation method of the sodium-ion battery hard carbon anode material of this embodiment, using semi-coke as raw material, the following steps are included in sequence:
[0055] (1) The semi-coke particles are mechanically crushed and screened through a 100-mesh sieve to obtain semi-coke powder.
[0056] (2) Add 4g of the semi-coke powder obtained in step (1) to 6mol / L concentrated hydrochloric acid and stir magnetically in a water bath at 35℃ for 12h.
[0057] (3) Wash the acid-treated semi-coke powder obtained in step (2) with water until neutral, and dry it to obtain acid-washed semi-coke powder.
[0058] (4) Place the pickled semi-coke powder obtained in step (3) into a muffle furnace and heat it at 3°C for 3 minutes under an air atmosphere. -1 The temperature was increased to 300℃ at a certain rate and held at this temperature for 3 hours, and then allowed to cool naturally to room temperature to obtain pre-oxidized semi-coke powder.
[0059] (5) Place the pre-oxidized semi-coke powder obtained in step (4) into a tubular carbonization furnace, and oxidize it at 3°C for 3 minutes under an argon atmosphere. -1 The temperature was increased to 1000℃ at a heating rate and held at this temperature for 2 hours, then continued at a rate of 3℃ / min. -1 The temperature was increased to 1300℃ at a heating rate and held at this temperature for 2 hours, then increased at a rate of 2℃ / min. -1 The temperature was lowered to 1000℃ at a cooling rate, and then allowed to cool naturally to room temperature to obtain a hard carbon anode material for sodium-ion batteries.
[0060] The hard carbon material obtained in step (5) was mixed with CNTs and sodium alginate binder (3.3% mass fraction) in a mass ratio of 8:1:1. The mixture was then loaded onto a copper foil current collector, vacuum dried for 12 hours, and cut into 12mm diameter discs for use as the negative electrode of the sodium-ion battery. The average mass loading of the active material was 1.5mg. The battery was then assembled in a glove box using the sodium disc as the counter electrode and glass fiber as the separator to obtain a CR2032 button cell. The assembled CR2032 button cell was left to stand in a constant temperature chamber for at least 12 hours before electrochemical performance testing. In this embodiment, a Land 2001A tester was used for constant current charge-discharge testing, with a metallic sodium disc as both the counter and reference electrode, and a voltage window of 0.01–3.00V. The test results showed that the material exhibited good electrochemical performance at a current density of 0.02Ag. -1 At that time, its capacity was 302mAh g.-1 .Depend on Figure 1 As shown, uniformly shaped pitch-based carbon microspheres were grown in situ on the surface of semi-coke-based hard carbon. Figure 2 It can be seen that the sample shows broad peaks at 24.3° and 43.1°, which correspond to the (002) and (100) diffraction crystal planes of graphite, respectively, indicating that the material is an amorphous carbon material. Figure 3 The initial charge / discharge curve shows that the charging capacity is greater than 300mAh g. -1 Furthermore, the first round coulomb efficiency is greater than 80%. Figure 4 The first recovery was 0.02Ag. -1 At a current density of 300 mAh g, the capacity rapidly recovers to 300 mAh g. -1 The above demonstrates its excellent cycling stability. The numerous carbon microspheres attached to the material surface provide ample sites for sodium ion adsorption, contributing to the capacity of the ramp region above 0.1V and improving rate performance. The stable spherical structure also contributes to the material's excellent long-cycle performance. Figure 5 0.05Ag -1 and 0.5Ag -1 The capacity retention rate is greater than 80% after 500 cycles.
[0061] Example 3
[0062] According to the preparation method of the sodium-ion battery hard carbon anode material of this embodiment, using semi-coke as raw material, the following steps are included in sequence:
[0063] (1) The semi-coke particles are mechanically crushed and screened through a 100-mesh sieve to obtain semi-coke powder.
[0064] (2) Add 4g of the semi-coke powder obtained in step (1) to 6mol / L concentrated hydrochloric acid and stir magnetically in a water bath at 35℃ for 12h.
[0065] (3) Wash the acid-treated semi-coke powder obtained in step (2) with water until neutral, and dry it to obtain semi-coke powder.
[0066] (4) Place the pickled semi-coke powder obtained in step (3) into a muffle furnace and heat it at 3°C for 3 minutes under an air atmosphere. -1 The temperature was increased to 300℃ at a certain rate and held at this temperature for 4 hours, and then allowed to cool naturally to room temperature to obtain pre-oxidized semi-coke powder.
[0067] (5) Place the pre-oxidized semi-coke powder obtained in step (4) into a tubular carbonization furnace, and oxidize it at 3°C for 3 minutes under an argon atmosphere. -1 The temperature was increased to 1000℃ at a heating rate and held at this temperature for 2 hours, then continued at a rate of 3℃ / min. -1The temperature was increased to 1300℃ at a heating rate and held at this temperature for 2 hours, then increased at a rate of 2℃ / min. -1 The temperature was lowered to 1000℃ at a cooling rate, and then allowed to cool naturally to room temperature to obtain a hard carbon anode material for sodium-ion batteries.
[0068] The hard carbon material obtained in step (5) was mixed with CNTs and sodium alginate binder (3.3% mass fraction) in a mass ratio of 8:1:1. The mixture was then loaded onto a copper foil current collector, vacuum dried for 12 hours, and cut into 12mm diameter discs for use as the negative electrode of the sodium-ion battery. The average mass loading of the active material was 1.5mg. The battery was then assembled in a glove box using the sodium disc as the counter electrode and glass fiber as the separator to obtain a CR2032 button cell. The assembled CR2032 button cell was left to stand in a constant temperature chamber for at least 12 hours before electrochemical performance testing. In this embodiment, a Land 2001A tester was used for constant current charge-discharge testing, with a metallic sodium disc as both the counter and reference electrode, and a voltage window of 0.01–3.00V. The test results showed that the material exhibited good electrochemical performance at a current density of 0.02Ag. -1 At that time, its capacity was 253mAh g. -1 The first lap efficiency was 80.7%.
[0069] Example 4
[0070] According to the preparation method of the sodium-ion battery hard carbon anode material of this embodiment, using semi-coke as raw material, the following steps are included in sequence:
[0071] (1) The semi-coke particles are mechanically crushed and screened through a 100-mesh sieve to obtain semi-coke powder.
[0072] (2) Add 4g of the semi-coke powder obtained in step (1) to 6mol / L concentrated hydrochloric acid and stir magnetically in a water bath at 35℃ for 12h.
[0073] (3) Wash the acid-treated semi-coke powder obtained in step (2) with water until neutral, and dry it to obtain acid-washed semi-coke powder.
[0074] (4) Place the pickled semi-coke powder obtained in step (3) into a muffle furnace and heat it at 3°C for 3 minutes under an air atmosphere. -1 The temperature was increased to 300℃ at a certain rate and held at this temperature for 6 hours, and then allowed to cool naturally to room temperature to obtain pre-oxidized semi-coke powder.
[0075] (5) Place the pre-oxidized semi-coke powder obtained in step (4) into a tubular carbonization furnace, and oxidize it at 3°C for 3 minutes under an argon atmosphere. -1The temperature was increased to 1000℃ at a heating rate and held at this temperature for 2 hours, then continued at a rate of 3℃ / min. -1 The temperature was increased to 1300℃ at a heating rate and held at this temperature for 2 hours, then increased at a rate of 2℃ / min. -1 The temperature was lowered to 1000℃ at a cooling rate, and then allowed to cool naturally to room temperature to obtain a hard carbon anode material for sodium-ion batteries.
[0076] The hard carbon material obtained in step (5) was mixed with CNTs and sodium alginate binder (3.3% mass fraction) in a mass ratio of 8:1:1. The mixture was then loaded onto a copper foil current collector, vacuum dried for 12 hours, and cut into 12mm diameter discs for use as the negative electrode of the sodium-ion battery. The average mass loading of the active material was 1.5mg. The battery was then assembled in a glove box using the sodium disc as the counter electrode and glass fiber as the separator to obtain a CR2032 button cell. The assembled CR2032 button cell was left to stand in a constant temperature chamber for at least 12 hours before electrochemical performance testing. In this embodiment, a Land 2001A tester was used for constant current charge-discharge testing, with a metallic sodium disc as both the counter and reference electrode, and a voltage window of 0.01–3.00V. The test results showed that the material exhibited good electrochemical performance at a current density of 0.02Ag. -1 At that time, its capacity was 231.5 mAh g. -1 The first lap efficiency was 81.2%.
[0077] Example 5
[0078] The difference between the preparation method of the sodium-ion battery negative electrode active material in this embodiment and the preparation method of the sodium-ion battery negative electrode active material in Example 2 is that the order of steps (4) and (5) is interchanged to obtain post-oxidation treated hard carbon material.
[0079] No obvious spherical morphology was observed in the SEM images. In this embodiment, constant current charge-discharge tests were performed using a Land 2001A tester, with a sodium metal sheet as both the counter and reference electrode, and a voltage window of 0.01–3.00 V. Figure 6 Test results show that the material exhibits good electrochemical performance at a current density of 0.02 Ag. -1 At that time, its capacity was 277mAh g. -1 The post-oxidation process resulted in abundant oxygen-containing functional groups on the surface of the hard carbon material, providing numerous surface adsorption sites for sodium ions. This led to an increase in the slope capacity ratio compared to the pre-oxidation treatment, with a slope capacity of 152 mAh·g. -1 It accounts for more than 50% of the reversible capacity, thus dominating the market. Simultaneously, it improves the rate performance of the material under high current (2A g). -1 50 mAh·g at current density -1It is suitable for power-type energy storage needs.
[0080] Comparative Example 1
[0081] The difference between the preparation method of the sodium-ion battery negative electrode active material in this comparative example and the preparation method of the sodium-ion battery negative electrode active material in Example 2 is that step (4) pre-oxidation step is removed.
[0082] This comparative example underwent constant current charge-discharge testing using a Land 2001A instrument, with a sodium metal sheet as both the counter and reference electrode, and a voltage window of 0.01–3.00 V. Electrochemical test results indicate that the material exhibits good electrochemical performance at a current density of 0.02 Ag. -1 At that time, its capacity was 266mAh g. -1 The efficiency of the first round of the game was 72%.
[0083] Comparative Example 2
[0084] The difference between the preparation method of the sodium-ion battery negative electrode active material in this comparative example and the preparation method of the sodium-ion battery negative electrode active material in Example 2 is that the carbonization step (5) is omitted. This comparative example uses a Land 2001A tester for constant current charge-discharge testing, with a metallic sodium sheet as the counter electrode and reference electrode, and a voltage window of 0.01–3.00 V. At a current density of 0.02 Ag... -1 At that time, its capacity was 180mAh·g -1 The initial coulombic efficiency was only 57.5%. This is related to the abundance of oxygen-containing functional groups and defects on the material surface, which contribute a large amount of irreversible capacity during the first cycle of the battery.
[0085] Comparative Example 3
[0086] The difference between the preparation method of the sodium-ion battery negative electrode active material in this comparative example and the preparation method of the sodium-ion battery negative electrode active material in Example 2 is only that the first heating and holding time in step (5) is removed, and the temperature is directly raised to the target temperature for carbonization. Figure 8 As shown, 0.5Ag -1 The capacity retention rate was only 75% after 500 cycles, which is related to the lack of carbon microsphere structure with cycle stability.
[0087] Comparative Example 4
[0088] The difference between the preparation method of the sodium-ion battery negative electrode active material in this comparative example and the preparation method of the sodium-ion battery negative electrode active material in Example 2 is that the particle size reduction method in step (1) is changed from mechanical crushing to high-energy ball milling.
[0089] Figure 9No obvious spherical morphology was observed in the SEM images. This comparative example underwent constant current charge-discharge testing using a Land 2001A instrument, with a sodium metal sheet as both the counter and reference electrode, and a voltage window of 0.01–3.00 V. The current density was 0.02 Ag. -1 At that time, its capacity was 252mAh g. -1 .
[0090] Comparative Example 5
[0091] The difference between the preparation method of the sodium-ion battery negative electrode active material in this comparative example and the preparation method of the sodium-ion battery negative electrode active material in Example 2 is that the particle size reduction method in step (1) is changed from mechanical crushing to vibrating ball milling.
[0092] Figure 10 No obvious spherical morphology was observed in the SEM images. This patent uses a Land 2001A tester for constant current charge-discharge testing, with a sodium metal sheet as both the counter and reference electrode, and a voltage window of 0.01–3.00 V. The test was conducted at a current density of 0.02 Ag. -1 At that time, its capacity was 262mAh g. -1 However, its Coulomb efficiency is only 68.6%.
Claims
1. A method for preparing a hard carbon anode material for sodium-ion batteries, characterized in that: Includes the following steps: (1) Mechanically crush the semi-coke particles, soak them in concentrated hydrochloric acid solution and stir to wash them, filter them with water until neutral, and dry them; (2) Pre-oxidation is carried out at a temperature of 250-350 ℃ for 2-6 h; (3) Under an inert atmosphere, the pre-oxidized semi-coke powder is heated to 800-1000℃ and held for the first stage of carbonization. Then, it is heated to 1200-1600℃ and held for the second stage of carbonization to obtain the hard carbon anode material for sodium-ion batteries. The carbonization heating rate is 1-5℃ / min. -1 The holding time for both the first and second carbonization stages is 1-3 hours, and the protective atmosphere is argon or nitrogen.
2. A method for preparing a hard carbon anode material for sodium-ion batteries, characterized in that: Includes the following steps: (1) Crush the semi-coke material, soak it in concentrated hydrochloric acid solution and stir to wash it, filter it with water until it is neutral, and dry it; the crushing method is mechanical crushing, vibrating ball milling or high-energy ball milling. (2) Under an inert atmosphere, the acid-washed semi-coke powder is heated to 800-1000℃ and held for the first stage of carbonization, and then heated to 1200-1600℃ and held for the second stage of carbonization. (3) Perform post-oxidation treatment at a temperature of 250-350℃ for 2-6 hours to obtain sodium-ion battery hard carbon anode material. The carbonization heating rate is 1-5℃ / min. -1 The holding time for both the first and second carbonization stages is 1-3 hours, and the protective atmosphere is argon or nitrogen.
3. A method for preparing a hard carbon anode material for sodium-ion batteries as described in claim 1 or 2, characterized in that: The concentration of the concentrated hydrochloric acid is 4-6 mol / L, the pickling temperature is 25-40℃, and the treatment time is 8-12 h.
4. The method for preparing a hard carbon anode material for sodium-ion batteries as described in claim 1, characterized in that: The pre-oxidation heating rate is 1-5℃ / min. -1 The pre-oxidation atmosphere is air.
5. A method for preparing a hard carbon anode material for a sodium-ion battery as described in claim 2, characterized in that: The post-oxidation heating rate is 1-5℃ / min. -1 The oxidizing atmosphere is then changed to air.
6. An electrode material, characterized in that: It includes conductive agents, binders, and the sodium-ion battery hard carbon anode material as described in claim 1 or 2.
7. A negative electrode sheet for a sodium-ion battery, characterized in that: Includes a current collector and the electrode material of claim 6 coated on the current collector.
Citation Information
Patent Citations
Carbon material for sodium-ion battery negative electrode, preparation method of carbon material, sodium-ion battery negative electrode plate and sodium-ion battery
CN114956037A
Biomass hard carbon negative electrode material and preparation method and application thereof
CN117208886A